Consumer Protection on Illegal Drugs Cases in Indonesia - Sari, Chatrin Intan (Indonesia Media Law Review, 2022)
The purpose of this study is to know how the legal protection for consumers on the circulation of illegal drugs and how the accountability of business actors on the circulation of illegal drugs. By using normative juridical research method is concluded: 1. Legal protection to consumers on the circulation of illegal drugs conducted by the government through the Agency of Drugs and Food (BPOM). With this BPOM shows the attention that the government has run its supervision. In addition, the protection of consumer law arising from the existence of rights and obligations set forth in Article 4 letters a and c, article 7 letters a and d, article 8 paragraph 1 letter a, d and e of Law Number 8 Year 1999 concerning Consumer Protection. The fulfillment of consumer rights over security, the right to be heard, the correct, clear and honest information regulated in the UUPK is still not fulfilled. Article 98 paragraph 2, Article 106 paragraph 1 and 2 of Law Number 36 Year 2009 on Health. 2. The business actor is responsible as the manufacturer of the goods because the importer of the goods is not an agent or official importer. The business actor who is an individual shall be liable for the losses incurred even if only as an importer not as a producer of the goods. Related to the violation of Article 8 paragraph 1 letter a, d and e then based on Article 62 paragraph 1 Laws that sanctions may be subject to imprisonment a maximum of five years or a maximum fine of Rp. 2,000,000,000 (two billion rupiah). It is thus a legal basis which can be worn by consumers as a form of accountability, addressed to businessmen illegal drugs is a criminal sanction sebagimana governed by article 62 paragraph 1 of BFL.